2004
DOI: 10.1002/joc.1012
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall and the length of the growing season in Nigeria

Abstract: This study examines the length of the growing season in Nigeria using the daily rainfall data of Ikeja, Ondo, Ilorin, Kaduna and Kano. The data were collected from the archives of the Nigerian Meteorological Services, Oshodi, Lagos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 14 publications
11
121
0
Order By: Relevance
“…Of the known factors influencing the climate of West Africa in general, and Nigeria in particular, the northward and southward migration of the ITD and its associated air masses (mT and cT) appear to be the most popularly accepted (Lamb, 1983;Adejuwon et al, 1990;Odekunle, 2004;Adejuwon and Odekunle, 2006). It has been established that rain falls mostly when an area is overlain by the mT air mass and ceases when the area is overlain by the cT air mass, thereby making the latitudinal position of the ITD a strong determinant of most rainfall attributes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the known factors influencing the climate of West Africa in general, and Nigeria in particular, the northward and southward migration of the ITD and its associated air masses (mT and cT) appear to be the most popularly accepted (Lamb, 1983;Adejuwon et al, 1990;Odekunle, 2004;Adejuwon and Odekunle, 2006). It has been established that rain falls mostly when an area is overlain by the mT air mass and ceases when the area is overlain by the cT air mass, thereby making the latitudinal position of the ITD a strong determinant of most rainfall attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, although rainfall is generally experienced in SSEZ between early June and the first ten days of September, its distribution characteristics are adequate for crop germination, establishment and development for roughly only two months -between the first ten days of July and the first five days of September (Odekunle, 2004). Apart from its short growing season, the ecological zone has a persistent and severe drought tendency (Nicholson, 2001;Paeth and Hense, 2006).…”
Section: The Sudano-sahelian Ecological Zone Of Nigeriamentioning
confidence: 99%
“…There is a clear contrast between the dry (January-February-March (JFM) and October-November-December (OND)) seasons and the wet (April-May-June (AMJ) and July-August-September (JAS)) seasons. The local impact of thunderstorms over the WS is usually sporadic, especially over the interior parts, mostly during the peak of the rain, usually during the JAS season (Odekunle, 2004;Idowu, 2007).…”
Section: Study Areamentioning
confidence: 99%
“…The WAM which is a moist and onshore maritime air from the Atlantic Ocean prevails over most of the WS in July while the dry and dusty offshore continental winds blowing across the Sahara desert toward the region prevails in January. There are a wide range of extensive convection and cloud developments within the ITD and accordingly five major weather zones (A to E) have been defined over the WS (see Ojo, 1977;Odekunle, 2004;Omotosho, 2008). More than 90% of the severe storms over WS especially during the peak of the rain (July-August-September) occur within the weather zone C, which is about 200 km south of the ITD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation